Construction of a finite element model of golf clubs and influence of shaft stiffness on its dynamic behavior - Tanaka, K.; Sekizawa, K. (Proceedings, 2018)
The objective of this study was to construct a finite element model for a carbon fiber reinforced plastic club shaft, and to investigate the effects of the torsional stiffness of the shaft on the dynamic behavior of a golf club during the swing. Mechanical properties of the shaft with orthotropic elasticity were determined using the rule of mixture which was defined by a volume fraction of fiber and resin. Swing simulations were conducted using club models with different torsional stiffness. The effect of the torsional stiffness on the clubhead alignment at impact tended to be stronger with the impact velocity of the clubhead due to the centrifugal force acting on the head. This indicates that the clubhead alignment at impact tends to be subject to effects of the timing of the impact, which depends on the relationship between the ball position and the impact velocity in addition to the mechanical properties of the shaft.